"The potential of social media in health promotion beyond creating awareness: an integrative review" - Atousa Ghahramani; Maximilian de Courten; Maria Prokofieva (BMC, 2022)
Abstract Background Developing strategies to change health behaviour is one of the biggest challenges of health promotion programs. Social media, as a popular and innovative communication and education tool, offers opportunities to modify health behaviour. While literature on using social media for health promotion campaigns is growing, there is a need to evaluate the approaches used to change health behaviour, rather than only creating awareness. Objective The paper reviewed the literature on application of social media in health promotion campaigns with a particular focus on the methodologies used in assessing the outcome of the programs for behaviour change. This fills the void in collating evidence to extend health promotion campaigns to effect sustainable behavioural change. Method Peer-reviewed articles were identified through multiple science databases. A systematic electronic search was conducted to retrieve review and original papers published between January 2010 and April 2022. The titles and abstracts of the articles were screened according to inclusion and exclusion criteria. All authors independently read the full texts and discussed them to reach a consensus about the themes. Concept mapping was used to present results from analysis of the included papers. Results Of the 674 citations, 28 (4.1%) studies were included in this review. The methodology approaches of 18 (2.7%) papers, that aimed to evaluate the impact of social media in health promotion campaigns towards behaviour change, were analysed further using concept mapping. The results showed that 10 studies (55.5%) adopted quantitative methods and five studies (27.7%) used mixed methods and three studies (16.6%) used qualitative methods. Facebook and YouTube were used more for intervention purposes to change health behaviour. Twitter and Instagram were used more to observe the trend of changes in health behaviour. Six studies (33.3%) adopted Social Cognitive Theory and one study (5.5%) applied the Transtheoretical Model as the framework to evaluate the outcome. Overall, the results show that though social media has potential in promoting behaviour change, the estimation of this change in long-term lies outside the scope of social media health campaigns. This is also reflected in the methodologies used in existing studies to assess such sustainable changes. The employed measures usually target immediate behaviour or social media engagement rather than addressing the change on a behavioural level. Conclusion Evaluating the performance of social media campaigns to promote health behaviours towards a sustainable outcome is a complex process. Emerging research is focused on evaluating the potential of social media as an opportunity to create awareness. Such measures require less effort in quantifying and isolating the effect. The design of the campaigns is required to be aligned in relation to stages of the behaviour change. The study provides suggestions on how this can be achieved.